INKONSISTENSI PENERAPAN MODEL PEMERINTAHAN DAERAH DI INDONESIA - Dawud, Drs. Joni (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2004)
Indonesia is still in the process of searching the most appropriate and ideal format and model of Local Government that can fulfill the needs of the nation. During the process, the changes carried out are often inconsistent and unstructured. Rather, they move from far left directly to far right, from decentralized to centralized and return to decentralized. The changes performed are not a revision, but rather it is remade and reformulated from the beginning. The most ironical situation is the change of national leader followed by the change of implementation concept of Local Government .